Open Seminar on Acoustics OSA’2006 - Engel, Zbigniew; Wiciak, Jerzy (Archives of Acoustics, 2006)
It is our pleasure to offer you papers submitted at the 53rd Open Seminar on Acoustics OSA’06 that was held in the charm and beautiful city of Zakopane, the highest located city in Poland, from September 11 to 15, 2006. The conference was organized jointly by the Polish Acoustical Society, Kraków Division, Committee of Acoustics, Polish Academy of Sciences and Department of Mechanics and Vibroacoutis, Faculty of Mechanical Engineering and Robotics at the AGH University of Science and Technology. The conference was attended by 160 scientists from Poland. There were 9 plenary lectures and over 120 contributed lectures. We continued with the tradition of poster presentation session to provide the maximum participation. This volume represents the diversity of contributions to the conference. We distinguished 11 different aspects of theoretical and experimental research in the field of acoustics. The papers are organized in an alphabetic order according to these topics: • biomedical acoustics • physical acoustics, • molecular and opto acoustics, • speech acoustics, • musical acoustics, • room acoustics, • environmental acoustics, • electroacoustics, • hydroacoustics, • transducers, • psychoacoustics. The Archives of Acoustics has developed a regular peer review system in the selection of submitted papers. The Organizing Committee has sought advice from two reviewers who are knowledgeable in the subject of the paper. We wish to express our special thanks to the referees for their active interest in the publishing of this book. We want also to thank the authors for preparing and correcting the manuscripts so that the most manuscripts were in acceptable form one month after the conference. We hope that these publications will be of interest of everyone and meet the expectations of the readers.